Strategi Pemerintah Dalam Meningkatkan UMKM Kota Palembang Di Masa Pandemi Covid-19 - Arwis Umairi; Novia Kencana; Amaliatulwalidain Amaliatulwalidain (Jurnal Pemerintahan dan Politik, 2021)
The purpose of this study is to find out how the strategies was carried out by the Government in increasing Usaha Kecil Mikro dan Menengah (UMKM) during the Covid-19  pandemic . The research method used by the author in this study is a qualitative method. The type of qualitative research used by the researcher in this study is a case study. The results of research and analysis of the Government's Strategy in Improving UMKM  in Palembang City during the Pandemic can be said to have gone well, it can be explained (1) Productive Assistance for Micro Enterprises provided by the government has helped and revived UMKM actors who have difficulty, especially in capital, (2 ) Equipment assistance distributed by the Cooperatives and UKM Office of Palembang City to UMKM is the right assistance as a necessity to run a business, (3) The manufacture and sale of cloth masks socialized by the Palembang City Cooperatives and UKM Service is an appropriate effort for UMKM actors those affected by the pandemic to continue to earn income, (4) Promotions carried out directly by regional officials on their personal social media accounts are very helpful for business actors in their promotion fields, plus the figure who promotes it is the number one person in South Sumatra. Keywords : government strategy, UMKM, Pandemic Time